The efficacy of the thyroid peroxidase marker for distinguishing follicular thyroid carcinoma from follicular adenoma - Savin, S.; Cvejic, D.; Isic, T.; Paunovic, I.; Tatic, S.; Havelka, M. (Experimental Oncology, 2006)
Aim: Expression of thyroid peroxidase (TPO) in the thyroid gland tissue is well known as a sensitive marker of the thyroid malignancy. We have evaluated immunohistochemical assay of TPO for distinguishing follicular thyroid carcinoma from follicular adenoma. Materials and Methods: Sections of formalin-fixed tissues obtained from 92 patients with thyroid tumors (52 follicular carcinomas and 40 follicular adenomas including the Hurthle cell type) were analyzed using a monoclonal antibody (TPO mAb 47) and the avidin-biotin peroxidase complex immunohistochemical technique. Lesions with staining of more than 80% of the follicular cells/specimen were considered benign, while less than 80% were considered malignant. Results: TPO immunostaining correlated with the histopathological diagnosis in 24/40 cases of follicular adenomas and 41/52 cases of follicular carcinomas, giving a specificity of 60% and a sensitivity of 79%. Conclusion: These results suggest that immunohistochemical assay of TPO expression has limited value for the differential diagnosis of follicular thyroid carcinoma from thyroid follicular adenoma.